The Influence of Traditional Games on the 50 Meter Short Distance Running Abilities of Class IV Students of SDN Kaliwungu 1 Jombang - Sulistyo, Yully Wahyu (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Traditional games are an exciting and fun teaching medium essential for children's physical growth. Short-distance running, where speed is critical, is an integral component of these games. This research aims to determine the effect of traditional games on the 50-meter short-distance running ability of class IV students at SDN Kaliwungu I Jombang. This research tests the hypothesis that conventional games significantly influence students' short-distance running abilities. This research uses a quantitative approach with an experimental design. The research population was all fourth-grade students at SDN Kaliwungu I Jombang, with the sample selected using a purposive sampling technique. Data was collected using pretest and posttest to measure students' running speed before and after treatment. Data analysis involves calculating standard deviation and significance tests (Sig. 2-tailed). Data analysis shows a significant increase in students' short-distance running abilities after being given traditional game treatment. The pretest results show a standard deviation of 6569; the lowest value is 3.3, and the highest is 6.3. Meanwhile, the posttest showed an increase with a standard deviation of 83338; the lowest value was 3.06, and the highest value was 7.45. The significant test shows the Sig value. (2-tailed) is 0.004 < 0.05 , so hypothesis H1 is accepted. Traditional games have a significant influence on students' short-distance running abilities. It is recommended that teachers use fun teaching media, such as traditional games, in learning and apply them to other subjects to increase learning effectiveness. This research is limited to a sample of fourth-grade students in one school. Future research needs to involve larger samples and a variety of locations for more general results.